FREQUENCY OF ELEVATED TROPONIN T IN PATIENTS OF CHRONIC RENAL FAILURE WITHOUT CLINICALLY SUSPECTED ACUTE MYOCARDIAL INFARCTION - Ali, Syed Affan; Kazmi, Sumera; Jalal-ud-din, Mir; Qasim, Muhammad Iqbal; Jadoon, Zahid Gul (Journal of Ayub Medical College Abbottabad, 2019)
Background: Cardiac Troponins are established markers of myocardial injury; however, they may be elevated in chronic renal failure (CRF) patients even in absence of acute myocardial infarction. The objective of the study was to determine the frequency of elevated Troponin T in patients of chronic renal failure without clinically suspected acute myocardial infarction. Methods: This cross-sectional study was conducted at Medical B Unit of Ayub Teaching Hospital, Abbottabad from 16th December 2013 to 16th June 2014. A sample of 117 patients of chronic renal failure was included in the study without any gender discrimination. The patients were defined as known chronic renal failure when renal failure was reported in their past medical history and by estimation of glomerular filtration rate (GFR). Those patients who had raised Troponin T due to any other reason like acute myocardial ischemia (chest pain, electrocardiographic changes and greater than 20% elevation in Troponin T from baseline), sepsis, heart failure and those who were receiving cardiotoxic chemotherapy were excluded. The subjects were enrolled by non-probability consecutive sampling. Results were analysed by SPSS 16.0 Results: Out of 117 participants, 72 (61.5%) were males and 45 (38.5%) were females. The mean age of the study participants was 52.08±14.21 years. Elevated Troponin T was found in 45 (38.5%) of the patients. There is statistically significant association between the stage of CRF and elevated levels of Troponin T. Statistically significant negative correlation (r=-0.213,p=0.021) was found between the Glomerular Filtration Rate and serum levels of Troponin T. Conclusion: A high proportion of CRF patients have elevated Troponin T and the rise is significantly associated with the stage of chronic renal failure. Keywords: Chronic renal failure, Troponin T, Acute myocardial infarction